Tolerogenic Dendritic Cells Reduce Cardiac Inflammation and Fibrosis in Chronic Chagas Disease - Santos, Emanuelle de Souza; Aragão-França, Luciana Souza de; Meira, Cássio Santana; Cerqueira, Jéssica Vieira; Vasconcelos, Juliana Fraga; Nonaka, Carolina Kymie Vasques; Pontes-de-Carvalho, Lain Carlos; Soares, Milena Botelho Pereira (Frontiers in Immunology, 2020)
Chronic Chagas disease cardiomyopathy (CCC) is the most frequent and severe form of this parasitic disease. CCC is caused by a progressive inflammation in the heart, resulting in alterations that can culminate in heart failure and death. The use of dendritic cells (DCs) appears as an option for the development of treatments due to their important role in regulating immune responses. Here, we investigated whether tolerogenic cells (tDC) could interfere with the progression of CCC in an experimental model of Chagas disease. The tDCs were generated and characterized as CD11b+ CD11c+ cells, low expression of MHC-II and CD80, and increased expression of PD-L1 and PD-L2. These cells produced low levels of IL-6 and IL-12p70 and higher levels of IL-10, compared to mature DCs (mDCs). Interestingly, tDCs inhibited lymphoproliferation and markedly increased the population of FoxP3+ Treg cells in vitro, compared to mature DCs. In a mouse model of CCC, treatment with tDCs reduced heart inflammation and fibrosis. Furthermore, tDCs treatment reduced the gene expression of pro-inflammatory cytokines (IL-6 and IL-12) and of genes related to cardiac remodeling (Col1a2 and Lgals3), while increasing the gene expression of IL-10. Finally, administration of tDCs, increased the percentage of Treg cells in the hearts and spleens of chagasic mice. Ours results show that tolerogenic dendritic cells have therapeutic potential on CCC, inhibiting disease progression.